Influence of pressure on piezoelectric, polarizing, and magnetic nature of SmFeO3: A DFT study. Issue 4 (17th September 2020) - Mubarak, Ahmad A.; Tariq, Saad
Abstract: In this article, we have presented structural, electronic, magnetic, mechanical, and optical attributes of SmFeO3 under pressure up to 80 GPa. These aforesaid properties are investigated by using state‐of‐the‐art density functional theory. The structural stability of the compound has been tested using the tolerance factor, enthalpy of formation, and elastic stability criteria of the elastic constants. Electronic band structure, the density of states, high magnetic moment, and Fermi surface analysis affirms the ferromagnetic nature of the studied compound throughout the pressure. We expect piezoelectric phenomena of the compound to be between 20 and 40 GPa pressure due to the increasing internal strain parameter with pressure. Moreover, the polarizing nature of the material is pressure‐dependent, which seems to decrease with an increase in pressure, while the minimum thermal conductivity of the compound is observed to be maximum along (110) direction, which increases with an increase in pressure. Our results suggested that the studied compound could be useful in the spintronic industry, in pressure‐dependent fast memory storage devices, and in piezoelectric sensors. Abstract : Fermi surface analysis of SFO (a) 0 GPa (b) 80 GPa.